Dynamic response and damage character of road embankment under strong earthquake - Jian Wang; Qimin Li; Changwei Yang; Caizhi Zhou (International Journal of Distributed Sensor Networks)
Dynamic response of road embankment under strong earthquake was explored by site investigation, shaking table tests, and discrete element method simulations, which shows that the distribution of responded accelerations strongly depends on the amplitude of input ground motion and the height of road embankment. When the peak ground acceleration of ground motion is small, peak ground acceleration amplification factors will linearly increase from the toe to the top of the slope; then, it will step into non-linear amplification; when the peak ground acceleration of ground motion is large enough, it will transform from amplification to attenuation. There is a logarithmic relationship between the magnitude of acceleration and the slope amplification factor, and the critical acceleration making the peak ground acceleration transform from amplification to attenuation increases with the raise of embankment height and connects with spectral characteristics of ground motion. There is a logarithmic relationship between the input ground acceleration and the amplification ratio of slope top to toe, and the critical acceleration making the peak ground acceleration transform from amplification to attenuation increases with the raise of embankment height and connects with spectral characteristics of ground motion. The results found should be useful for aseismic of road embankment as well as railway subgrade.